Analisis Faktor yang Memengaruhi Kebutuhan Ber-KB dengan Pendekatan Social Cognitive Theory (Studi di Kecamatan Genteng Surabaya) - Nurul Ainia (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
Increased population growth was a problem faced by Indonesia. One of reason is because of the high unmet need for family planning. This research analyzed Influence factor family planning needs based on social cognitive theory. The research was quantitative study with a cross sectional design. Samples were married woman with the age of 15–49 years who don’t to have children or postpone their pregnancy either by using contraception or not as many as 70 womans and taken by simple random sampling. The independent variable were observational learning, outcome expectation, self efficacy, husband support, access to information, and access to health services. The dependent variable of this study was family planning needs. Quantitative data were analyzed using binary logistic regression test. A quarter of respondents were of unmet need for family planning. There was influence observational learning, husband support, and access information to family planning needs. This research concluded that was the determinant factor that influence to family planning need was access to information.